Psycho-aesthetic Concept of A.V. Bakushinsky and Periodization of Human Ontogenesis - N.E. Veraksa; L.F. Bayanova; E.O. Shishova (Культурно-историческая психология)
Interest in the work of A.V. Bakushinsky stems from the significance of his psycho-aesthetic concept for contemporary developmental psychology. This concept outlines the stages of mental development associated with a child's perceptual capabilities within the context of global fine art. The article presents an argument supporting A.V. Bakushinsky’s commitment to the cultural-historical approach in evaluating ontogenesis. A.V. Bakushinsky illustrates the parallels between the means of global fine art and the use of artistic symbols by children in their visual activities, following the developmental patterns of the child's psyche. The article also offers a comparative analysis of the approaches taken by A.V. Bakushinsky and A.V. Zaporozhets. They assess the evolution of perception. The similarities and differences in the conclusions of A.V. Bakushinsky and O.M. Dyachenko regarding the formation of images as symbolic means in ontogenesis are examined. A.V. Bakushinsky's ideas hold practical significance for elucidating the perception of the diversity of information, which the scientist called the “multiplicity of the world.” The findings of this study can be used by specialists in the design and evaluation of a developmental educational environment.